Dynamic mechanical analysis of suspended soft bodies via hydraulic force spectroscopy. Issue 4 (29th November 2022) - Berardi, Massimiliano; Gnanachandran, Kajangi; Jiang, Jieke; Bielawski, Kevin; Visser, Claas W.; Lekka, Małgorzata; Akca, B. Imran
Abstract : We present a new approach for the microrheological characterization of soft suspended bodies. We obtain results comparable to AFM based dynamic nanoindentation. We discuss viscoelastic and poroelastic contributions to material behavior. Abstract : The rheological characterization of soft suspended bodies, such as cells, organoids, or synthetic microstructures, is particularly challenging, even with state-of-the-art methods ( e.g. atomic force microscopy, AFM). Providing well-defined boundary conditions for modeling typically requires fixating the sample on a substrate, which is a delicate and time-consuming procedure. Moreover, it needs to be tuned for each chemistry and geometry. Here, we validate a novel technique, called hydraulic force spectroscopy (HFS), against AFM dynamic indentation taken as the gold standard. Combining experimental data with finite element modeling, we show that HFS gives results comparable to AFM microrheology over multiple decades, while obviating any sample preparation requirements.